Microsatellite genotyping of contributing broodstock and selected offspring of Haliotis midae submitted to a growth performance recording scheme - Ruivo, Nicola Ribeiro (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.